2020
DOI: 10.3390/rs12233920
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Ganoderma boninense in Oil Palm Seedlings Using Support Vector Machines

Abstract: Ganodermaboninense (G. boninense) is a fungus that causes one of the most destructive diseases in oil palm plantations in Southeast Asia called basal stem rot (BSR), resulting in annual losses of up to USD 500 million. The G. boninense infects both mature trees and seedlings. The current practice of detection still depends on manual inspection by a human expert every two weeks. This study aimed to detect early G. boninense infections using visible-near infrared (VIS-NIR) hyperspectral images where there are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…However, the procedures entail stem collection, which may result in plant damage and eventual destruction. Other proposed methods used include an electronic nose (e-nose) [15,16], electrical impedance [17,18], tomography [19,20], thermal imaging [21,22], multispectral imaging [23,24], spectroscopy or hyperspectral data [25][26][27][28][29][30], and a terrestrial laser scanner (TLS) [31][32][33][34][35]. A comprehensive review of sensors used to detect BSR by [36] has found that each technique has different scores in terms of accuracies and limitations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the procedures entail stem collection, which may result in plant damage and eventual destruction. Other proposed methods used include an electronic nose (e-nose) [15,16], electrical impedance [17,18], tomography [19,20], thermal imaging [21,22], multispectral imaging [23,24], spectroscopy or hyperspectral data [25][26][27][28][29][30], and a terrestrial laser scanner (TLS) [31][32][33][34][35]. A comprehensive review of sensors used to detect BSR by [36] has found that each technique has different scores in terms of accuracies and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The infected seedlings demonstrate lower reflectance in the NIR range (750-950 nm) compared to healthy seedlings as a result of xylem destruction, which thus causes a reduction of chlorophyll pigments and a water deficiency. Based on the research work done by [26], the use of SVM with 18 and 35 NIR-hyperspectral wavelengths could provide 100% accuracy of G. boninense detection when the spectral reflectance was extracted from frond number 1 of the seedlings. The percentage accuracy was slightly reduced to 94% when fronds number 1 and 2 were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive remote sensing techniques, including ground-based, airborne, and space-borne remote sensing, have also been investigated to identify and map BSR-infected trees. Recent studies have demonstrated that hyperspectral and multispectral remote sensing methods can distinguish healthy and BSR-infected trees [14][15][16][17][18][19][20]. Terrestrial laser scanning (TLS) [21][22][23], synthetic aperture radar (SAR) data [24,25], intelligent electronic nose (E-Nose) systems [26,27], tomographic sensors [28,29], and microfocus X-ray fluorescence [30] also showed positive results in detecting BSR-infected trees.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early detection methods are urgently required. Only a few methods have been reported to detect this disease before symptoms manifest as fruiting bodies, including enzyme-linked immunosorbent assay (ELISA) (Kayalvizhi and Antony, 2011;Utomo and Niepold, 2000;Kandan et al 2009;Siddiqui et al 2021), polymerase chain reaction (PCR) (Chong et al 2011;Midot et al 2019;Bahari et al 2018;Goh et al 2016), sequencing (Hayati and Basyuni, 2019), laser machine learning (ML) through laser beam scanning (Husin et al 2020), hyperspectral imagery visible near-infrared (VIS-NIR) (Azmi et al 2020;Ahmadi et al 2017;Isha et al 2019), scanning electron microscopy (Alexander et al 2017), and network detection through Ganoderma selective media (GSM) network (Rakib et al 2014;Darus and Seman, 1992;Penido et al 2013). Furthermore, weeds as markers of the organism's presence based on dominant species have also been reported (Saragih and Purba, 2018), with the nutrients in weed leaves compared to infected and uninfected oil palm (Saragih and Purba, 2019).…”
Section: Introductionmentioning
confidence: 99%